Psychological pain tolerance mediates the association between physical pain sensitivity and suicidal ideation: a cross-sectional study - Meng Liang; Huijing Xu; Qian Jiang; Taosheng Liu (BMC Psychiatry)
Abstract Background Previous studies have consistently identified pain as a significant risk factor for suicidal behavior. Both physical and psychological pain have been implicated in the underlying mechanisms of suicidal behavior. Guided by the interpersonal theory of suicide, this study assessed how physical pain sensitivity and psychological pain tolerance jointly shape vulnerability to suicidal ideation in college students. Methods Using a cross-sectional design, 1013 college students were surveyed via standardized questionnaires, yielding 846 analyzable responses. Suicidal behavior was assessed using the Suicide Behavior Screening Questionnaire (SBSQ). Physical pain sensitivity and psychological pain tolerance were evaluated using the Pain Sensitivity Questionnaire (PSQ) and the Tolerance of Mental Pain Scale (TMPS-10), respectively. The relationships among physical pain sensitivity, psychological pain tolerance, and suicidal behavior were analyzed. Additionally, the mediating role of psychological pain tolerance in the relationship between physical pain sensitivity and suicidal behavior was examined. Results Compared to participants without suicidal ideation, those with suicidal ideation exhibited significantly higher physical pain sensitivity (p = 0.011) and significantly lower psychological pain tolerance (p < 0.001). A linear regression analysis revealed a correlation between physical pain sensitivity and psychological pain tolerance (B = -0.095, p = 0.006). Logistic regression analysis indicated that both physical pain sensitivity (B = 0.369, odds ratio (OR) = 1.446, p = 0.038) and psychological pain tolerance (B = -0.676, OR = 0.509, p < 0.001) were associated with suicidal ideation. Mediation analysis showed that psychological pain tolerance partially mediated the relationship between physical pain sensitivity and suicidal ideation. However, logistic regression analysis revealed that physical pain sensitivity did not significantly predict suicidal attempts, while psychological pain tolerance remained a significant predictor. Conclusions The study demonstrated that psychological pain tolerance is associated with both suicidal ideation and suicide attempts, whereas physical pain sensitivity is only associated with suicidal ideation. Psychological pain tolerance partially mediates the effect of physical pain sensitivity on suicidal ideation. Reducing physical pain sensitivity or increasing psychological pain tolerance may be effective strategies for lowering the risk of suicidal ideation.